Islamic home financing and the real sectors in Malaysia: An ARDL bound testing approach to cointegration - Mohd Yusof, Rosylin (IIUM Press, 2015)
This study examines the dynamic relationship between macroeconomic variables (i.e., gross domestic product, house prices, stock prices, and interest rate) and home financing provided by Islamic banks in Malaysia.Using quarterly data from 2007 to 2014, this study employs autoregressive distributed lag (ARDL) bound testing cointegration approach, impulse response function (IRF), and forecast error variance decomposition (FEVD) to analyze the long-run and short-run relationships between selected macroeconomic variables and amount of Islamic home financing.This study finds that macroeconomic variables have distinct long-run and short run influence on Islamic home financing.Our findings reveal that policy intervention to stimulate or dampen home financing provided by Islamic banks, in the long run, can focus on GDP, house prices, and monetary policy. This further underscores the link between the real sector of the economy and bank lending by Islamic banks. In addition, this study documents evidence that Islamic home financing in Malaysia, at least in the short run, is not dependent on interest rate and hence, calls for a potential alternative rate, possibly rental rate, that can be used as a benchmark rather than the current conventional interest rate.To a certain extent, the findings suggest that Islamic banks are non interest based and have managed to live up to their ideals in achieving the objectives of Sharīʿah (maqāṣid alSharīʿah) by promoting real sectors to increase Islamic home financing.This study is among the very few studies that empirically examine the nexus between Islamic home financing and real sector of the economy.